METHODOLOGY OF TEACHING ENGLISH BASED ON INTERCULTURAL COMMUNICATION - Shaxzoda Ortikova (Modern American Journals, 2025)
The article examines the methodology of teaching English through the lens of intercultural communication, emphasizing the integration of cultural awareness into language education. In today’s globalized academic and social environment, the ability to communicate across cultures has become as essential as linguistic competence itself. The study highlights the importance of developing intercultural communicative competence among learners, which includes not only language proficiency but also sensitivity to cultural values, beliefs, and social norms. The paper discusses the theoretical foundations of intercultural communication, its role in English language teaching (ELT), and the pedagogical principles that guide its implementation. Various methods such as project-based learning, authentic materials, simulations, and digital interactions are analyzed as tools to enhance learners’ intercultural understanding. The research concludes that intercultural methodology enriches the teaching process by creating meaningful, real-world contexts that prepare students for active participation in multicultural communication.
Keywords: Intercultural communication, English language teaching, cultural competence, communicative skills, teaching methodology